PENGEMBANGAN PRODUKSI BIOHIDROGEN DARI KELAPA SAWIT ATAU LIMBAH SEBAGAI BAHAN BAKAR FUEL CELLUNTUK PEMBANGKIT LISTRIK DAERAH TERPENCIL - Irhan Febijanto; Mahyudin Abdul Rahman; Eniya Listiani Dewi (Jurnal Energi dan Lingkungan (Enerlink), 2011)
Indonesia is the country which produces the biggestamount CPO (Crude Palm Oil) in the world. The production would be larger in the next 10 years. The biggest amount of abundant palm oil waste is also produced, such as shell, empty fruit bunch for solid waste and POME (palm oil mill waste) for water waste.Â  All waste produces methane gas which is contributing GHG (Green HouseÂ  Gasses) emission. In this study, waste palm oil waste substituted by glycerol is fermented using Enterobacter Aerogens ADH43 to produces bio-H2. The bio-H2is purified by carbon dioxide, CO2 and water, H2O using zeolit and silica absorber and Ca(OH)2 solvent, respectively, before flew it to fuel cell. In order to produce bio-H2, the compact fermentor was equipped in this study. It is shown from the study result that Enterobacter Aerogens could growth and produced bio-H2, continuously. The electricity could be generated from fuel cell by flew purified bio-H 2constantly to the fuel cell.Kata kunci: abundant palm waste, bio-H2, electricity, fuel cell, fermentor